Idarubicin combats abiraterone and enzalutamide resistance in prostate cells via targeting XPA protein - Ying Zhang; Wei Wei; Changying Li; Siyuan Yan; Shanshan Wang; Shudong Xiao; Chenchen He; Jing Li; Zhi Qi; Benyi Li; Kuo Yang; Changlin Li (Cell Death and Disease, 2022)
Abstract Although second-generation therapies like abiraterone (ABI) and enzalutamide (ENZ) benefit patients with castration-resistant prostate cancer (CRPC), drug resistance frequently occurs, eventually resulting in therapy failure. In this study, we used two libraries, FDA-approved drug library and CRISP/Cas9 knockout (GeCKO) library to screen for drugs that overcome treatment resistance and to identify the potential drug-resistant genes involved in treatment resistance. Our screening results showed that the DNA-damaging agent idarubicin (IDA) overcame abiraterone and enzalutamide resistance in prostate cancer cells. IDA treatment inhibited the DNA repair protein XPA expression in a transcription-independent manner. Consistently, XPA knockout sensitized prostate cancer cells to abiraterone and enzalutamide treatment. In conclusion, IDA combats abiraterone and enzalutamide resistance by reducing XPA protein level in prostate cancer.